The effect of informational on anxiety level of first time mother with caesarean section - Srisuying , Arunee; Phuakphan , Wilailak (Journal of Nursing, Siam University, 2025)
This quasi-experimental study aimed to compare the levels of anxiety related to the cesarean section between primigravida who received informational support and those who received standard nursing care. The sample consisted of 78 primigravida divided into a control group (39 participants) and an experimental group (39 participants). Participants were aged between 20-34 years, had normal pregnancies of 37 - 42 weeks, and were experiencing their first pregnancy. The research instruments included (1) a 20-item maternal anxiety assessment scale for cesarean section and (2) a personal information recording form. The reliability of the instruments was tested using Cronbach’s alpha coefficient, yielding a value of .85. Data was analyzed using descriptive statistics and t-tests to compare anxiety levels before and after the intervention, both within and between groups. The findings revealed that primigravida who received informational support had reduced anxiety levels after receiving information about the cesarean section. The mean anxiety scores between the two groups showed a statistically significant difference at the .001 level. The study suggests that providing informational support regarding cesarean sections before surgery can help reduce anxiety among pregnant women.